Autologous stem cell transplantation (ASCT) as a consolidation of remission in peripheral T-cell lymphoma (PTCL) – the preliminary results of the first 11 patients - Stella-Hołowiecka, Beata; Wieczorkiewicz, Agata; Helbig, Grzegorz; Bober, Grażyna; Wojciechowska, Maria; Najda, Jacek; Kachel, Lucja; Hołowiecki, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2007)
Background: Peripheral T-cell lymphomas show aggressive course and poor outcome. High-dose chemotherapy is thought to improve outcome in these patients, but the role of up-front ASCT is still unclear. Material and methods: 11 patients (5 male/6 female); median age at ASCT was 41 years. The CHOP regimen was administered as an induction treatment. The median number of chemotherapy regimens needed to achieve CR or PR was 8 (range 3-20). 7 patients (64%) achieved complete remission before ASCT; 4 showed PR. The conditioning regimen was CBV for 10 patients and 1 patient received BEAM. Results: The median number of mononuclear cells was 3.5 × 108/kg (range 2.02-6.9); median CD34+ cell dose infused/kg was 6.2 × 106/kg (range 1.1-17.2). Engraftment of neutrophils >0.5 × 109/l was observed at a median of 14 days (range 12-18), engraftment of platelets >50 × 109/l was achieved in a median of 16 (range 10-30). The 100-day mortality rate was 0%. 4 out of 11 patients (36%) developed progression/relapse after ASCT after a median of 7 months (range 4-9). 3 out of 4 patients died in disease progression, 1 patient underwent allogeneic stem cell transplantation. Only 1 out of 7 patients transplanted in CR had an early relapse occurring 4 months after ASCT. With a median of 20 months (range 6-52) of follow-up 6 patients (55%) remain in CR. The estimated probability of 3-year overall survival (OS) and progression-free survival (PFS) is 60% and 62% respectively. Conclusions: Up-front ASCT in PTCL is highly effective, but further study with a large post-transplant population are needed to confirm the results.